Methodology of 5G network planning and design for vertical industry with product solutions - Ziyu XIAO; Hongwei LV; Cun ZHAO; Yan HAN; Jian SU (Dianxin kexue)
The methodology of 5G toB network planning was discussed.The current situation of 5G network was introduced and the challenges of network planning were analyzed for vertical industry requirements with diversification and customization.Then the methodology of 5G toB scenario-oriented planning and design was put forward, based on the network technology system, oriented the future business layout of the industry, focused on the planning ability of accurate identification, on-demand delivery and network elasticity, so as to achieve the goal of on-demand planning and agile network construction.At the same time, on the basis of methodology, an end-to-end planning and design platform algorithm was proposed to achieve the collaborative planning for toC (public network) and toB (vertical network).